Immune modulation by a tolerogenic myelin oligodendrocyte glycoprotein (MOG)10–60 containing fusion protein in the marmoset experimental autoimmune encephalomyelitis model. (April 2015) - Kap, Y. S.; van Driel, N.; Arends, R.; Rouwendal, G.; Verolin, M.; Blezer, E.; Lycke, N.; 't Hart, B. A.
Summary Current therapies for multiple sclerosis (MS), a chronic autoimmune neuroinflammatory disease, mostly target general cell populations or immune molecules, which may lead to a compromised immune system. A more directed strategy would be to re‐enforce tolerance of the autoaggressive T cells that drive tissue inflammation and injury. In this study, we have investigated whether the course of experimental autoimmune encephalomyelitis (EAE) in mice and marmosets can be altered by a potent tolerizing fusion protein. In addition, a multi‐parameter immunological analysis was performed in marmosets to assess whether the treatment induces modulation of EAE‐associated cellular and humoral immune reactions. The fusion protein, CTA1R9K‐hMOG10–60‐DD, contains a mutated cholera toxin A1 subunit (CTA1R9K), a dimer of the Ig binding D region of Staphylococcus aureus protein A (DD), and the human myelin oligodendrocyte glycoprotein (hMOG) sequence 10–60. We observed that intranasal application of CTA1R9K‐hMOG10–60‐DD seems to skew the immune response against myelin oligodendrocyte glycoprotein (MOG) towards a regulatory function. We show a reduced number of circulating macrophages, reduced MOG‐induced expansion of mononuclear cells in peripheral blood, reduced MOG‐induced production of interleukin (IL)‐17A in spleen, increased MOG‐induced production of IL‐4 and IL‐10 and an increased percentage of cells expressing programmed cell death‐1 (PD‐1) and CC chemokine receptor 4 (CCR4). Nevertheless, the treatment did not detectably change the EAE course and pathology. Thus, despite a detectable effect on relevant immune parameters, the fusion protein failed to influence the clinical and pathological outcome of disease. This result warrants further development and improvement of this specifically targeted tolerance inducing therapy.